2016
DOI: 10.1123/jpah.2014-0597
|View full text |Cite
|
Sign up to set email alerts
|

The Canadian Assessment of Physical Literacy: Development of a Model of Children’s Capacity for a Healthy, Active Lifestyle Through a Delphi Process

Abstract: The revised CAPL model (overlapping domains of physical competence, motivation, and knowledge, encompassed by daily behavior) is appropriate for monitoring the physical literacy of children aged 8 to 12 years. Objectively measured domains (daily behavior, physical competence) have higher relative importance. The interpretation of CAPL results should be reevaluated as more data become available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
4
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(116 citation statements)
references
References 0 publications
1
108
4
3
Order By: Relevance
“…Health education in an organized way that targets the young population may be best implemented at school, which provides the best setting for delivering public health interventions at a young age. In particular, physical development of school children could be based on physical literacy that addresses attributes, characteristics, skills, and behaviors that are related to the ability for, and commitment to, a healthy, active lifestyle [53]. From the military perspective, these interventions could also be modeled to capture physical capacity (e.g., physical endurance) and psychological resilience (e.g., resistance to stress) and to emphasize the importance of avoiding substance use or abuse.…”
Section: Alcohol Consumption and Nutritionmentioning
confidence: 99%
“…Health education in an organized way that targets the young population may be best implemented at school, which provides the best setting for delivering public health interventions at a young age. In particular, physical development of school children could be based on physical literacy that addresses attributes, characteristics, skills, and behaviors that are related to the ability for, and commitment to, a healthy, active lifestyle [53]. From the military perspective, these interventions could also be modeled to capture physical capacity (e.g., physical endurance) and psychological resilience (e.g., resistance to stress) and to emphasize the importance of avoiding substance use or abuse.…”
Section: Alcohol Consumption and Nutritionmentioning
confidence: 99%
“…CAPL is the first valid, reliable and comprehensive protocol in Canada for monitoring actual levels of PL among Canadian children [11]. The development progress of the assessment underwent a three-round Delphi expert review and then confirmed the model as the CAPL [12]. Recently, the research group has updated the model in a second edition, the CAPL-2.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of the Delphi process is to reach a consensus on a specific research issue after multiplied rounds of discussions. For this present study, a consensus was defined as agreement among 75% or more of the panel [35]. Each round was implemented by a webpage and reminder e-mails from November 2017 to March 2018.…”
Section: Procedures Of the Delphi Processmentioning
confidence: 99%